Impacts of high-electroactive-surface-area buckypaper counter electrodes on the photovoltaic performance of dye-sensitized solar cells. (9th September 2015) - Cheng, Cheng-En; Lin, Yu-Chang; Tsai, Shang-Yi; Lin, Zheng-Kun; Lee, Ping-Chen; Miao, Hsin-Yuan; Chang, Chen-Shiung; Chien, Forest Shih-Sen
Abstract In this paper we study the photovoltaic performance of dye-sensitized solar cells (DSCs) with high-electroactive-surface-area buckypaper (BP) counter electrodes (CEs). BP is made of entangled multi-walled carbon nanotubes and has a high electroactive surface area, which is effectively 11.5 times higher than that of Pt. The high surface area of BP causes a high <?CDATA I_3^- ?> <?MML I3− ?><inline-graphic xlink:href="ark:/27927/pgj2j5x4dq8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> reduction rate at the CEs and suppresses the charge recombination at the anodes. Accordingly, the open-circuit voltage, the filling factor, and the power conversion efficiency of DSCs with BP CEs are enhanced, and these photovoltaic parameters exhibit a better trend with the increase of solar power compared with conventional DSCs with Pt CEs.